Role of LDL-C level alteration in increased mortality risks in spontaneous intracerebral hemorrhage patients: Systematic review and meta-analysis - Li, Jing; Li, Gang; Zhu, Yajun; Lei, Xingwei; Chen, Guihu; Zhang, Jiachun; Sun, Xiaochuan (Frontiers in Neurology, 2023)
Background: Current studies indicate a contradictory relationship between decreased mortality risks of spontaneous intracerebral hemorrhage (sICH) and elevated low-density lipoprotein cholesterol (LDL-C) levels. Thus, this meta-analysis was designed to examine the involvement of high LDL-C levels in a lower mortality risk of sICH patients. Methods: PubMed, Cochrane, and Embase databases were searched up to the date of August 3rd, 2022. Pooled odds ratio (OR) with a 95% confidence interval (CI) was estimated for the lower versus higher serum LDL-C level groups. Subgroup and sensitivity analyses were also carried out. Egger’s test was applied to detect any potential publication bias. Results: Of 629 citations reviewed, 8 eligible cohort studies involving 83,013 patients were enrolled in this meta-analysis. Compared with lower serum LDL-C levels containing patients, higher serum LDL-C patients exhibited significantly decreased risks of 3-month mortality (OR: 0.51; 95%CI: 0.33-0.78; I2=47.8%); however, the LDL-C level change wasn’t significantly associated with in-hospital mortality risks (OR: 0.92; 95%CI: 0.63-1.33; I2=91.4%) among sICH subjects. All studies included were classified as high-quality investigations. Conclusions: This meta-analysis suggests a higher LDL-C level may decrease the mortality risk in sICH patients. LDL-C level increase is inversely associated with the 3-month mortality risks in these patients but not significantly correlated with the in-hospital mortality risks. Further well-designed prospective studies with extended follow-up periods are needed to confirm these findings and explore underlying cross-talks.